PENERAPAN TRADEMARK DILUTION PADA PENEGAKAN PERLINDUNGAN HUKUM HAK MEREK TERKENAL DI INDONESIA - Joko Setiyono (Law Reform: Jurnal Pembaharuan Hukum, 2019)
ABSTRACT The aims of study to analyze the rules of well-known/famous protection related trademark dilution doctrine and discuss the change for the application of trademark dilution doctrine in the enforcement of the well-known mark protection in Indonesia. The research method used is normative juridical with descriptive analysis approach. Data sources are secondary data and analysis methods used qualitative analysis. Research results show that the change to apply the trademark dilution, consist in the process of registration the mark and in the case of the cancellation of rights of mark. The examiner of mark, ex-officio or at request on the well-known mark owner to refusal or to cancel for trademark registration that has identic or resembles for the well-known mark of the use non similar goods taking into account the reputation of the well-known mark. The lack of rules regarding trademark dilution which is clearly regulated in the Trademark Law is the reason the judges have not been able to apply the trademark dilution doctrine. Without any reason for blurring or tarnisment, the aim is to cancel the same or similar of the well-known mark by other non-competitor parties within reached